Competitive Aggressiveness and Its Role in The Growth of Public Transport Enterprises in Kenya - Eshiwani Martin Onyango; Patrick Karanja Ngugi; Samson Nyang’au (Integrasi Sains Media, 2024)
This study investigates the influence of competitive aggressiveness on the growth of public transport enterprises in Kenya. Public transport enterprises significantly contribute to the national economy, yet they encounter numerous challenges in their operating environment, such as evolving policies, regulatory changes, taxation issues, poor infrastructure, and inconsistent law enforcement, all impacting growth. While competitive aggressiveness is often deemed crucial for entrepreneurial success, exploring its effects in the Kenyan public transport sector is limited. This study addresses this gap, grounded in the resource-based view (RBV) theory of competitiveness. Employing a descriptive-correlational research design, the study surveyed all 261 public transport enterprises operating in Nairobi County. Data were collected via questionnaires and analyzed using SPSS, applying descriptive and inferential statistical methods. Results indicate a significant positive effect of competitive aggressiveness on enterprise growth (? = 0.704; p < 0.05). The study concludes that low levels of competitive aggressiveness among public transport entrepreneurs limit sectoral growth. It recommends fostering a more aggressive competitive approach to support enterprise expansion within this critical sector.